2019
DOI: 10.1080/14786419.2019.1643859
|View full text |Cite
|
Sign up to set email alerts
|

Isolates From Thymelaea Hirsuta Inhibit Progression Of Hepatocellular Carcinoma In Vitro And In Vivo

Abstract: Herein, we investigated effect of Thymelaea hirsuta isolates on hepatocellular carcinoma. Methanolic extract of T. hirsuta led to isolation of two new compounds [6` hydroxyDaphnoretin (9) and Mithnin (15)], seven compounds reported for the first time from genus Thymelaea [Dotriacontanol (1), and 3-ketopentatriacontanoic (2),Docosylcoumarate (5), Docosylcaffeate (6), Daphnodorin B (11), 3`` -epidihydrodaphnodorin B (12) and Wikstaiwanone B ( 14)], and six known compounds.Eight compounds (5, 6, 9, 10, 11, 12, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…This is crucial for cancer cells to maintain their uncontrollable proliferation. Therefore, triggering apoptosis is a main mode of action for most of the anti-cancer agents [16,17,19,[42][43][44][45]. In the present study, A. machrostachyum extract reduces EST size through induction of apoptosis as evidenced histologically (presence of apoptotic cells), and molecularly (up-regulation of the apoptotic genes p53, Bax, and caspase 3, and downregulation of the antiapoptotic gene Bcl2 as well as increase DNA damage).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…This is crucial for cancer cells to maintain their uncontrollable proliferation. Therefore, triggering apoptosis is a main mode of action for most of the anti-cancer agents [16,17,19,[42][43][44][45]. In the present study, A. machrostachyum extract reduces EST size through induction of apoptosis as evidenced histologically (presence of apoptotic cells), and molecularly (up-regulation of the apoptotic genes p53, Bax, and caspase 3, and downregulation of the antiapoptotic gene Bcl2 as well as increase DNA damage).…”
Section: Discussionmentioning
confidence: 50%
“…The notable therapeutic outcomes of some medicinal plants and/or their phytochemicals lifted the bar for other synthetic drugs that could lead to severe adverse effects [9][10][11]. The cytotoxic effect of many medicinal plants against cancer cells is primarily owed to induction of apoptosis mainly through upregulation of the apoptotic genes (such as p53, Bax, caspase 3, 7, 8, and 9) and downregulation of the anti-apoptotic genes (Bcl2 and survivin) [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This result was in line with the finding of Kakengi et al, (2003); Olugbemi and Banjo (2012) who found that the inclusion of M. oleifera meal in the diet of the broilers significantly enhanced their weight gain at 1% level which was significantly higher than the control. Several research findings reported that herbal extracts could increase broiler performance by improving live weight gain (Al-Kassie and Jameel, 2009;Badawy et al, 2019;Jamroz et al, 2003).…”
Section: Body Weight Gainmentioning
confidence: 99%
“…Natural products derived from plants have served as an important source of pharmacologic agents for several diseases [ 2 ], including cancer [ 3 ]. An example is the Thymelaeaceae family of plants, that have been shown to exhibit many pharmacological activities [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. For example, extracts of Daphne giraldii [ 4 ] and Wikstroemia indica [ 5 ] from the Thymelaeaceae family of plants are known to contain various pharmacologically active constituents, including: flavonoids [ 6 ], coumarins [ 7 ], diterpenoids [ 8 ], lignans, volatile oils and polysaccharides [ 9 ] that have been used for the tretament of several ailments.…”
Section: Introductionmentioning
confidence: 99%
“…T. hirsute contains flavonoids, coumarins, tannins, and saponins [ 13 ], and has been demonstarted to have antiviral activity against HIV-1 [ 14 ], antioxidant activity [ 15 ], antidiabetic and antihypertensive activities [ 16 ]. Other studies have also shown isolates from T. hirsuta to have significant cytotoxicity against hepatocellular carcinoma (HCC) [ 17 ], which is one of the leading causes of cancer deaths worldwide, with a rapidly increasing incidence rate in Egypt [ 18 ].…”
Section: Introductionmentioning
confidence: 99%